Integrated Metabolomics and Transcriptomic Analysis of Cellular Stress Responses: Elucidating Metabolic Pathways and Regulatory Networks - Askary, Gul Rukh; Khan, Zafar Ahmad; Azim, Syeda Samira; Parveen, Syeda Asiya; Zufishan, Shayan; Alam, Syed Munawar (Indus Journal of Bioscience Research, 2024)
Cellular stress responses are vital for maintaining homeostasis and enabling adaptation to environmental and physiological challenges. This study employed an integrated metabolomic and transcriptomic approach to investigate the regulatory networks and metabolic pathways underlying these responses. Conducted between July 2023 and December 2024 in Karachi, Pakistan, the research utilized cutting-edge technologies, including real-time PCR, high-performance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), and next-generation sequencing (NGS). Biological samples representing various stress conditions, such as oxidative stress, nutrient deprivation, and environmental stressors, were collected and analyzed under strict ethical protocols.RNA sequencing (RNA-Seq) revealed 1,250 differentially expressed genes (DEGs), with notable upregulation of GPX1 and SOD2, indicating enhanced detoxification pathways under oxidative stress. Concurrently, metabolomic profiling identified significant alterations in metabolites, such as elevated glutathione, lactate, and proline, highlighting adaptive shifts in glycolysis, reactive oxygen species (ROS) detoxification, and osmoprotection. Integrative analysis using Weighted Gene Co-expression Network Analysis (WGCNA) pinpointed key regulatory hubs, including HIF1A and succinate, as central nodes in stress-specific networks.This comprehensive multi-omics approach provided actionable insights into the molecular and metabolic mechanisms of cellular stress. The findings hold significant translational potential in agriculture and medicine, particularly for enhancing crop resilience and developing targeted therapies for stress-related disorders. Despite the limitations of in vitro models, this study underscores the value of multi-layered omics analyses in elucidating stress adaptation and lays the groundwork for future integrative research